Association between osteoporosis and gallstone based on the National Health and Nutrition Examination Survey (NHANES) 2017–2020: a cross-sectional study - Li, Chuang; He, Qifan (Frontiers in Public Health, 2025)
BackgroundOsteoporosis and gallstones are both common conditions in older adults, yet the association between them remains unclear. This study investigates the relationship between osteoporosis and gallstones in a large, nationally representative sample of U.S. adults using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2020.Methods7,766 participants aged 50 years or older with complete osteoporosis questionnaire or bone mineral density (BMD) data included in the study. Osteoporosis status was determined based on self-reported physician diagnosis and femoral neck BMD measurements. Logistic regression models were used to examine the association between osteoporosis and gallstone risk, adjusting for sociodemographic, lifestyle, and health-related covariates. Generalized additive models (GAM) and smoothing curve fitting were used to explore the non-linear relationship between femoral neck T-scores and gallstone prevalence. Mediation analysis was performed to investigate the roles of serum calcium and phosphorus in mediating the osteoporosis-gallstone association.ResultsOur analysis revealed a significant association between osteoporosis and an increased risk of gallstones, particularly among individuals aged 65 and older, non-Hispanic whites, those with a college education or higher, and those with comorbid conditions such as hypertension and diabetes. In multivariate logistic regression models, individuals with osteoporosis had a higher risk of gallstones compared to those without osteoporosis (OR: 1.52, 95% CI: 1.15–1.99, p < 0.001). Further analysis based on femoral neck BMD indicated that osteoporosis (T-score ≤ −2.5) was significantly associated with an increased risk of gallstones (OR: 1.67, 95% CI: 1.11–2.46, p = 0.01). Generalized additive model analyses revealed a nonlinear relationship between femoral neck T-scores and gallstone prevalence. Mediation analysis indicated that serum calcium and phosphorus partially mediated the association between osteoporosis and gallstones.ConclusionThis study demonstrates a significant association between osteoporosis and an increased risk of gallstones in older adults. Our findings highlight the importance of routine gallstone screening for individuals with osteoporosis, particularly those with additional risk factors. Femoral neck BMD may serve as a more effective marker of gallstone risk than lumbar spine BMD.